8(2n-1)=6(6n+3)+8

Simple and best practice solution for 8(2n-1)=6(6n+3)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2n-1)=6(6n+3)+8 equation:


Simplifying
8(2n + -1) = 6(6n + 3) + 8

Reorder the terms:
8(-1 + 2n) = 6(6n + 3) + 8
(-1 * 8 + 2n * 8) = 6(6n + 3) + 8
(-8 + 16n) = 6(6n + 3) + 8

Reorder the terms:
-8 + 16n = 6(3 + 6n) + 8
-8 + 16n = (3 * 6 + 6n * 6) + 8
-8 + 16n = (18 + 36n) + 8

Reorder the terms:
-8 + 16n = 18 + 8 + 36n

Combine like terms: 18 + 8 = 26
-8 + 16n = 26 + 36n

Solving
-8 + 16n = 26 + 36n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-36n' to each side of the equation.
-8 + 16n + -36n = 26 + 36n + -36n

Combine like terms: 16n + -36n = -20n
-8 + -20n = 26 + 36n + -36n

Combine like terms: 36n + -36n = 0
-8 + -20n = 26 + 0
-8 + -20n = 26

Add '8' to each side of the equation.
-8 + 8 + -20n = 26 + 8

Combine like terms: -8 + 8 = 0
0 + -20n = 26 + 8
-20n = 26 + 8

Combine like terms: 26 + 8 = 34
-20n = 34

Divide each side by '-20'.
n = -1.7

Simplifying
n = -1.7

See similar equations:

| 3/-4 | | 5p-16=10 | | -7x-12=2x-(5x-8) | | (k-8)/(4+k)=-0.2 | | 7+n/8=n | | 0=a-49 | | ((-3j-(-4))/-6)-8=12 | | -3x+4-2x=7x | | -7-10=3f-10 | | -y/4=-10 | | 16x=0.5 | | -1(z+5)=-1 | | 50+7x-6=13x-4 | | 2x^5/2+5x^3/2=7x^1/2 | | 12=3b-5b | | -7f-10=3f-10 | | 7/1(4/1) | | 7/1(4/1) | | -1(2+5)=-14 | | 53y=2 | | 4n^2-2=14 | | -3n=7n+10 | | 22x+2y=-20 | | 5a+45a+23b+5=25a+3b+56 | | 4/3x=6 | | 15y+10=160+40y | | 96=-6x+5(-x-5) | | 2x(x+1)=7 | | 8p-1+p=10p-9 | | 2z-3=53+9z | | 4+3y=-12 | | -17=4x+12-9x |

Equations solver categories